2005
DOI: 10.1007/s00418-005-0761-x
|View full text |Cite
|
Sign up to set email alerts
|

Orexin inputs to caudal raphé neurons involved in thermal, cardiovascular, and gastrointestinal regulation

Abstract: Orexin-expressing neurons in the lateral hypothalamus with their wide projections throughout the brain are important for the regulation of sleep and wakefulness, ingestive behavior, and the coordination of these behaviors in the environmental context. To further identify downstream effector targets of the orexin system, we examined in detail orexin-A innervation of the caudal raphe nuclei in the medulla, known to harbor sympathetic preganglionic motor neurons involved in thermal, cardiovascular, and gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 69 publications
1
79
0
Order By: Relevance
“…Long-lasting effects and interference with the diurnal rhythm are not exclusive among the peptides regulating energy balance. Orexin initiates daytime food intake only, and NPY's action on body temperature is maintained for at least 24 h. 24,25 Earlier data showed that nesfatin-1 reduced nocturnal food intake in the first 6 h after icv injections or given intranasally at the beginning of the dark phase. 1,3 Report about longer than 24 h observations is not published so far.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting effects and interference with the diurnal rhythm are not exclusive among the peptides regulating energy balance. Orexin initiates daytime food intake only, and NPY's action on body temperature is maintained for at least 24 h. 24,25 Earlier data showed that nesfatin-1 reduced nocturnal food intake in the first 6 h after icv injections or given intranasally at the beginning of the dark phase. 1,3 Report about longer than 24 h observations is not published so far.…”
Section: Discussionmentioning
confidence: 99%
“…Orexin (also known as hypocretin) is a neuropeptide that has been reported to play a role in the regulation of feeding, drinking, body temperature, general activity (Lubkin and Stricker-Krongrad, 1998;Edwards et al, 1999;Hagan et al, 1999;Kunii et al, 1999;Mondal et al, 1999;Piper et al, 2000;Estabrooke et al, 2001;Hungs et al, 2001;Yoshimichi et al, 2001;Kotz et al, 2002;Berthoud et al, 2005), energy homeostasis (Mintz et al, 2001), stimulation of gastric secretion in rats (Takahashi et al, 1999), increasing metabolic rate in rats (Lubkin and Stricker-Krongard, 1998), altering luteinising hormone release in rats (Pu et al, 1998) and in the regulation of the sleepwake cycle specifically associated with increased wakefulness and inhibition of REM sleep (Sakurai et al, 1998;Chemelli et al, 1999;Siegel, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Thannickal et al, 2000;van den Pol, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Axons of orexin-containing neurons project to respiration-related sites, such as the nucleus tractus solitarius, pre-Bötzinger complex, and the hypoglossal, raphe, retrotrapezoid, and phrenic nuclei (Berthoud et al 2005;Fung et al 2001;Peyron et al 1998;Young et al 2005). Intracerebroventricular administration of orexin promotes respiration (Zhang et al 2005) and orexin-deficient mice exposed to stressors increase their respiration less as compared to control mice (Kayaba et al 2003;Zhang et al 2006b).…”
Section: Orexinmentioning
confidence: 99%